Teacher peer support in social network sites. (May 2016) - Kelly, Nick; Antonio, Amy
Abstract: This paper describes the types of support that teachers are accessing through the Social Network Site (SNS) 'Facebook'. It describes six ways in which teachers support one another within online groups. It presents evidence from a study of a large, open group of teachers online over a twelve week period, repeated with multiple groups a year later over a one week period. The findings suggest that large open groups in SNSs can be a useful source of pragmatic advice for teachers but that these groups are rarely a place for reflection on or feedback about teaching practice. Highlights: Presents a study of teachers' peer support within open groups in social network sites. Teachers in large, open Facebook groups offer predominantly pragmatic advice and social support. Teachers in these groups are not reflecting on practice, giving feedback or modelling practice. Results are found to be repeatable in other Facebook groups of teachers.